Некоторые аспекты рыночного понимания инвестиционной деятельности - Kovshov A. S. (Science and education: future development, 2017)
It reflects some aspects of market understanding of investment activity on the example of the Republic of Karelia as a factor of social and economic potential of the region. It is shown that nearly three quarters of the budget allocated to investment in fixed assets, up from the federal budget.
Keywords: инвестиционная деятельность; Республика Карелия; investment; Republic of Karelia; рыночное понимание; market understanding